Profile of Students' Creative Thinking Skills in Learning Physics on the Topic of Linear Motion - Rahmawati Rahmawati; Mirna Mirna; Khaeruddin Khaeruddin (Radiasi : Jurnal Berkala Pendidikan Fisika, 2022)
This study aimed to analyze the level of senior high school students’ creative thinking skills in the line movement topic. This type of research was expost facto research. Subjects in this study were 28 senior high shcool students in one of the South Sulawesi schools. The research instrument used was a test in the essay question form. The results of this research showed that the average score of creative thinking skills was medium category with a percentage of 61%. The study results showed that the most prominent indicator was elaborate thinking with an average score of 15.93 and the lowest indicator was thinking fluently with an average score of 11.14 compared to other indicators. From the results of the study, it was concluded that the creative thinking skills of students were in the medium category. There was a suggestion that the next researcher can continue with creative thinking skills test questions with other materials. In addition, further research can also be carried out by providing innovative learning that trains creative thinking skills so that students are able to develop their creative thinking skills.